Discerning Cultural Depictions and Mistakes in Kafe Piter, a Russian Language Textbook for Finnish Students - Mironenko, Olga (fi=Turun yliopisto|en=University of Turku|, 2016)
This thesis presents the results of an analysis of the content in the series of Russian textbooks Kafe Piter, which is widely used in Finnish educational institutions for adult learners at the time that the research is conducted. The purpose of this study is to determine and describe how a textbook may purvey an image of a foreign country (in this case, Russia). Mixed-methods research with a focus on the qualitative content analysis of Kafe Piter is performed. The guidelines for textbook evaluation of cultural content proposed by Byram (1993) are used in this study as the basis for creating a qualitative analysis checklist, which is adopted according to the needs of the current research. The selection of the categories in the checklist is based on major themes where direct statements about Russia, Russian people and culture appear in the textbook. The cultural content and the way in which it is presented in Kafe Piter are also compared to the intercultural competence objectives of the Common European Framework of Reference for Languages. Because the textbook was not written by a native Russian speaker, it was also important to investigate the types of mistakes found in the books. A simple quantitative analysis in the form of descriptive statistics was done, which consisted of counting the mistakes and inaccuracies in Kafe Piter. The mistakes were categorized into several different groups: factual or cultural, lexicosemantic, grammatical, spelling and punctuation mistakes. Based on the results, the cultural content of Kafe Piter provides a rich variety of cultural information that allows for a good understanding of the Russian language and Russian culture. A sufficient number of cross-cultural elements also appear in the textbook, including cultural images and information describing and comparing Russian and Finnish ways of life. Based on the cultural topics covered in Kafe Piter, we conclude that the textbook is in line with the intercultural competence objectives set out in the Common European Framework of Reference for Languages. The results of the study also make it clear that a thorough proofreading of Kafe Piter is needed in order to correct mistakes - more than 130 cultural and linguistic mistakes and inaccuracies appear in the textbook.